The Relation of Democratic Parenting and Health Behavior to students of sanata dharma university - Andhika, Patrick; Widodo, Yohanes Heri (SOLUTION, 2023)
The purpose of this study is to: (1) Knowing the relation between democratic parenting and health behavior to students of Sanata Dharma University. (2) Knowing how healthy or good the healthy living behavior of Sanata Dharma University students is. (3) Knowing the high and low levels of democratic parenting in Sanata Dharma students. (4) Knowing the items of democratic parenting and healthy living behavior that are identified as low,so that they can be proposed as guidance topics. The research used is correlative quantitative type.Thisstudy uses the subject of Sanata Dharma University students from various faculties and study programs at Sanata Dharma University. The number of respondents in this study amounted to 110 students and this study used a linkert scale. The democratic parenting scale used was made by Afra Sonia S.Pd with a total of 39 valid items and has an Alpha Cronbach reliability index of 0.947. The scale of the next variable is healthy living behavior, totaling 28 valid statement items and has an Alpha Cronbach reliability index of 0.726. Hypothesis testing that has been carried out in this study shows the correlation value of Spearman's rho which is 0.033 and r of 0.203 so that this study has concluded that the two variables have a significant relationship. Therefore, the hypothesis that there is a positive relationship between democratic parenting and healthy living behavior in Sanata Dharma University students is proven to have a relationship. This study has the results: (1) there is a significant relationship between democratic parenting and healthy living behavior in Sanata Dharma University students. (2) Democratic parenting in Sanata Dharma University students is classified as very democratic or very high democratic parenting received by SanataDharma University students with a percentage of 48%. (3) The healthy living behavior of Sanata Dharma University students is classified as good with a percentage of 57%. (4) There are 8 suggestions forguidance topics because there are 8 item statementsthat are identified aslow